Gambaran Status Gizi Remaja di SMA Negeri 2 Kendari Provinsi Sulawesi Tenggara - Irma Yunawati (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Adolescents are a vulnerable age group to nutritional problems due to increased nutritional requirements during periods of rapid growth. Suboptimal nutritional status, including undernutrition and anaemia, can negatively affect health and academic performance. This study aimed to describe the nutritional status of adolescents at SMA Negeri 2 Kendari, Southeast Sulawesi Province. This study employed a descriptive observational design conducted from August to September 2025 with a total sample of 226 twelfth-grade students’ selected using proportionate stratified random sampling. Data were collected through measurements of body weight and height to determine nutritional status based on the BMI-for-Age indicator and haemoglobin levels were assessed using a digital haemometer. Data were analyzed using univariate analysis. The results showed that most respondents had normal nutritional status (52.2%), while a considerable proportion were undernutrition (47.8%). In addition, more than half of the respondents were anaemia (50.9%). These findings indicate that although anthropometric nutritional status was generally normal, anemia remains a health problem that requires attention among adolescents. Regular monitoring of nutritional status and hemoglobin levels accompanied by nutrition education is recommended. Further studies are recommended to use an analytical study design to identify factors associated with nutritional status and anaemia.